Endothelial cationic amino acid transporter‐1 overexpression blunts the effects of oxidative stress on pressor responses to behavioural stress in mice. (December 2014) - Rajapakse, Niwanthi W; Konstantinidis, George; Evans, Roger G; Nguyen‐Huu, Thu‐Phuc; Kaye, David M; Head, Geoffrey A
Summary Observational studies indicate that psychological stress may contribute to the pathogenesis of hypertension and this may be further accentuated by factors such as endothelial dysfunction. On this basis, we aimed to determine whether oxidative stress enhances pressor responses to stressful stimuli and whether augmenting endothelial function by increasing the transport of l‐arginine can counter the effects of oxidative stress. Telemetry probes were used to measure mean arterial pressure (MAP) in wild‐type (WT; n = 6) and endothelial cationic amino acid transporter‐1 (CAT‐1)‐overexpressing (CAT+) mice (n = 6) before and during an aversive (restraint) and non‐aversive (almond feeding) stressor. The superoxide dismutase inhibitor diethyldithiocarbamic acid (DETCA; 30 mg/kg per day; 14 days) was then administered via a minipump to induce oxidative stress. Stress responses to feeding and restraint were repeated during Days 11–12 of DETCA infusion. In WT mice, pressor responses to restraint and feeding were augmented during infusion of DETCA (35 ± 1 and 28 ± 1 mmHg, respectively) compared with respective pretreatment responses (28 ± 2 and 24 ± 1 mmHg, respectively; P ≤ 0.01). In CAT+ mice, pressor responses to feeding were blunted during DETCA (20 ± 1 mmHg) compared with the control response (23 ± 1 mmHg; P = 0.03). In these mice, pressor responses to restraint were similar before (28 ± 1 mmHg) and during (26 ± 1 mmHg) DETCA infusion (P = 0.26). We conclude that endothelial CAT‐1 overexpression can counter the ability of oxidative stress to augment pressor responses to behavioural stress.